Local atomic order of a metallic glass made visible by scanning tunneling microscopy. (23rd May 2018) - Luo, Yuansu; Samwer, Konrad
Abstract: Exploring the atomic level structure in amorphous materials by STM becomes extremely difficult due to the localized electronic states. Here we carried out STM studies on a quasi-low-dimensional film of metallic glass Zr65 Cu27.5 Al7.5 which is 'ultrathin' compared with the localization length and/or the length scale of short range order. The local electronic structure must appear more inherent, having states at E f available for tip-sample tunneling current. To enhance imaging contrasts between long-range and short-range orders, the highly oriented pyrolytic graphite was chosen as substrate, so that the structural heterogeneity arising from competition between the glass former ability and the epitaxy can be ascertained. A chemical order predicted for this system was observed in atomic ordered regimes (1–2 monolayers), accompanied with a superstructure with the period Zr–Cu(Al)–Zr along three hexagonal axes. The result implies a chemical short range order in disordered regimes, where polyhedral clusters are dominant with the solute atom Cu(Al) in the center. An attempt for the structural modelling was made based on high resolution STM images, giving icosahedral order on the surface and different Voronoi clusters in 3D space.